Regulatory Response to Self-production of Energy: A Risk for the Development of Renewable Sources and Combined Heat and Power - Di Pillo, Francesca; Introna, Vito; Levialdi, Nathan; Marchegiani, Laura (International Journal of Energy Economics and Policy, 2018)
The high price for electrical energy increasingly leads companies to engage in self-production, so as to reduce costs, increase their own energy efficiency, and achieve market competitiveness. In general such self-production solutions have positive environmental impacts, since they involve exploitation of renewable sources and high-yield cogeneration plants, as well as avoiding inefficiencies due to network losses. However, the resulting reduction in the network exchange of electrical energy does not lead to proportional reductions in the network costs, and finding adequate coverage for these remains a necessity. Given this context, the role of the regulator becomes fundamental. The regulator must implement strategies for purposes of meeting national needs in regards to costs, but without excessively penalizing the companies and their international competitiveness, and without holding back development of environmentally favourable and sustainable solutions. The current article analyzes the possible regulatory interventions, their technical and organizational difficulties, and the impacts of these strategies in the national context. Keywords: energy self-production; renewable sources; CHP; network costs; general system fees; regulatory interventions JEL Classifications: L5, Q2, Q4